2019
DOI: 10.1097/shk.0000000000001436
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Vasodilation by Intravenous Infusion of Organic Mononitrites Of 1,2-Propanediol in Acute Pulmonary Hypertension Induced by Aortic Cross Clamping and Reperfusion: A Comparison With Nitroglycerin in Anesthetized Pigs

Abstract: Introduction: Suprarenal aortic cross clamping (SRACC) and reperfusion may cause acute pulmonary hypertension and multiple organ failure. Hypothesis: The organic mononitrites of 1,2-propanediol (PDNO), an nitric oxide donor with a very short half-life, are a more efficient pulmonary vasodilator and attenuator of end-organ damage and inflammation without significant side effects compared with nitroglycerin and inorganic nitrite in a porcine SRACC model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…However, PDNO completely counteracted the increase in systemic vascular resistance, an effect that was not present in the Control group. The known IAH effect on MPAP was confirmed in the present study [ 7 ]. It was evident that PDNO significantly delayed the MPAP increase whereas placebo did not.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…However, PDNO completely counteracted the increase in systemic vascular resistance, an effect that was not present in the Control group. The known IAH effect on MPAP was confirmed in the present study [ 7 ]. It was evident that PDNO significantly delayed the MPAP increase whereas placebo did not.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, organic nitrite NO-donors are associated with less tolerance development and have therefore been presented as an attractive alternative. Previously, we designed a novel NO-donor, comprising the organic mononitrites of 1,2-propanediol, nitrosooxypropanol (PDNO), and found that it was an effective vasodilator in some different models of acute pulmonary hypertension [7,[9][10][11], and that it ameliorated renal ischemia reperfusion injury [12]. A phase I study in humans is ongoing (Eura-daCT No.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, the effect of changes in vascular stiffness in blood pressure and WSS was investigated numerically. While vasodilation is known as the most important way to control hypertension (Giles, Sander, Nossaman, & Kadowitz, 2012), its side effects are always controversial (Nilsson et al, 2020), (Okada et al, 2020). Therefore, finding the causes and roots of hypertension and its symptoms can be an effective step in determining the treatment strategy.…”
Section: Discussionmentioning
confidence: 99%